Infusing Positive Psychological Interventions Into Career Counseling for Diverse Populations. (February 2019) - Owens, Rhea L.; Flores, Lisa Y.; Kopperson, Caitlin; Allan, Blake A.
Using the strengths-based inclusive theory of work as a framework, this paper describes how positive psychological interventions (PPIs) can be infused within career and work counseling for diverse populations. Exemplar constructs targeted in the interventions include hope, strengths, adaptability, and empowerment. First, we discuss research related to hope, strengths, adaptability, and empowerment interventions, particularly studies related to career counseling. Second, we describe considerations and recommendations related to adapting PPIs for diverse groups. Finally, a case vignette is shared to demonstrate how PPIs and adapted PPIs might be infused when working with a client seeking career counseling.